2017
DOI: 10.1016/j.psyneuen.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status discrimination and C-reactive protein in African-American and White adults

Abstract: Objectives We examined the association between socioeconomic status (SES) discrimination and C-reactive protein (CRP) in a biracial cohort of middle-aged adults using an intersectionality framework. Methods Participants were 401 African-American and White adults from a population-based cohort in the Southeastern United States. SES discrimination was self-reported with a modified Experiences of Discrimination Scale, and CRP levels were assayed from blood samples. Linear regression analyses were used to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 61 publications
(81 reference statements)
2
29
0
Order By: Relevance
“…The EOD scale was modified with an additional question regarding discrimination “while staying in a shelter, SRO, or residential treatment.” For each of the aforementioned settings, the 10‐item EOD asked (yes/no) “Have you ever experienced discrimination, been prevented from doing something, or been hassled or made to feel inferior because of your gender identity or presentation, or race ethnicity or color?” Each question verifying setting‐based discrimination was followed by a question clarifying if the experienced discrimination was related to gender identity or presentation, race/ethnicity or both. Situation scores for gender identity, race and both gender identity and race were skewed and therefore dichotomized (yes/no) as in past studies . Cronbach's alpha was 0.76 for the present study.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…The EOD scale was modified with an additional question regarding discrimination “while staying in a shelter, SRO, or residential treatment.” For each of the aforementioned settings, the 10‐item EOD asked (yes/no) “Have you ever experienced discrimination, been prevented from doing something, or been hassled or made to feel inferior because of your gender identity or presentation, or race ethnicity or color?” Each question verifying setting‐based discrimination was followed by a question clarifying if the experienced discrimination was related to gender identity or presentation, race/ethnicity or both. Situation scores for gender identity, race and both gender identity and race were skewed and therefore dichotomized (yes/no) as in past studies . Cronbach's alpha was 0.76 for the present study.…”
Section: Methodsmentioning
confidence: 83%
“…Each question verifying setting-based discrimination was followed by a question clarifying if the experienced discrimination was related to gender identity or presentation, race/ethnicity or both. Situation scores for gender identity, race and both gender identity and race were skewed and therefore dichotomized (yes/no) as in past studies [15]. Cronbach's alpha was 0.76 for the present study.…”
Section: Experiences Of Discrimination Scalementioning
confidence: 80%
“…To calculate BMI, height and weight were measured to the nearest 0.5 cm using a Health O Meter mechanical beam scale and height rod. Waist circumference was measured at the top of the iliac crest, to the nearest 0.5 cm. Immune : Previous research has confirmed the validity of salivary CRP measurement and its association with psychological stress and health (Dhingra et al, 2007, Truba et al, 2018, Van Dyke et al, 2017). We measured CRP using the third in-office saliva sample and analyzed the biomarker using the Enzyme-linked Immunosorbent assays (ELISAs) from Salimetrics LLC, Carlsbad, CA, USA.…”
Section: Methodsmentioning
confidence: 98%
“…Potential confounders (assessed at Examination 1) were selected based on the existing literature regarding factors related to discriminatory experiences, adiposity, and systemic inflammation. Age in years, 23 biological sex, 18 and educational attainment 17 (less than high school; high school diploma or GED; or attended trade school, vocational school, or college) were self-reported. Self-reported smoking 23 was categorized based on American Heart Association criteria: poor (current smokers), intermediate (quit <12 months ago), and ideal (quit ≥12 months ago or never smokers).…”
Section: Methodsmentioning
confidence: 99%